교통소음의 특성비교와 방음벽 설치를 위한 조사연구 - 최배진 (연세대학교 보건대학원, 1990)
[한글] 산업사회의 급속한 변화는 환경을 오염시키고 있다. 그 중에서 소음의 문제는 인구의 증가, 도시의 집중화 및 교통량의 증가로서 도로의 소음이 심각한 사회문제화 되고 있는 시점에서 본 연구에서는 방음벽 효과 및 설치를 위한 연구대상으로서 경부 고속도로 3개 지점과 중부고속도로로 3개 지점 그리고 APT지역으로 목동과 과천 주공 APT를 설정하였고 철도 소음영향 지역으로는 인천 만석동에 경인전철 주변을 조사지역으로, 그리고 설치를 위해서 광주 운암 APT와 인천 태양 아파트를 설정하였다. 소음 측정 방법은 공해공정시험법에 준하여 측정하였고 방음벽 차음효과는 방음벽을 중심으로 전후 1m지점에서 측정한 값으로서 분석하였다. 교통인자는 차속, 총 통행량, 혼입율, 도로구배, 그리고 도로 종류를 고려하여 교통소음과의 상관 관계를 분석처리하였다. 소음원으로서는 자동차 소음과 철도소음을 대상으로 측정 분석하였다. 또한 이들 소음이 방음벽 종류별로 아파트 층수에 미치는 영향에 대하 여 조사하였다. 이와 같이 소음을 측정하여 조사한 결과 방음벽효과는 잔향실법에 의해 측정한 투과 손실치와 현장에서 측정한 방음벽의 투과 손실치 사이에 15 d8(A) 내외의 오차가 발생한 것을 알 수 있었다. 즉, 잔향실법에 의한 투과손실치보다 현장에서 측정한 값이 더 크게 나 타났다. 교통인자관계는 자동차 소음에 영향을 주는 인자중 상관계수가 0.965가 되는 차속과 총교통량과의 관계식을 도출하였다. 철도소음에서 진입시와 진출시 상이함을 비교하여 보았다. 진출시는 저주파에서부터 차츰 소음도가 증가하다가 2000H^^z 부근에서 감소하고 진입시는 저주파100∼1000H^^z사이에서 74.0 dB(A) 에서부터 82.0 dB(A) 의 높은 소음도가 나타나고 있다. 철도 소음에서 아파트에 미치는 영향을 비교하여 보았는데, 1층 · 3층 사이에는 7-8 dB(A) 이상의 차음효과가 있는 반면, 4 · 5층에서는 변화가 없었다. 일본의 신간선 철도소음 환경기준인 70 dB(A)와 비교하여 보면, 4층이상에서는 3.7 dB(A)∼7.8 dB(A) 의 기 준치 초과 현상이 나타난다. 교통인자 상관관계는 차속(X)와 총통행량(Y)에서 Y = -5.47 X + 722의 관계식을 가지며 상관계수는 (Coefficient of correlative)은 0.965로서 좋은 결과를 얻었다. 즉 역함수관계를 나타내주고 있으며 일정한 차선을 갖는 도로에서 교통량이 증가하면 차속이 감소 하고 차속이 증가하면 교통량이 적어야 한다는 결론에 도달한다. 도로구배와 소음도 및 주파수 특성을 그림 4와 같이 살펴보면 저주파 영역에서는 구배차에 의한 소음도차이가 비교적 적지만 500H^^z -2000H^^z 영역에서는 구배에 따라 약 20 dB(A) 증감하는 현상이 나타났다. 이것은 가속에 따른 엔진소음의 영향으로 생각된다. Study on the barriers effect for the traffic noise chracteristies BAE JIN CHOI Dep. of Environmental Science Graduate School of Health Science and Management YONSEI UNIVERSITY (Supervised by professor SUK PYO KWON Ph.D) The study evaluated the barrier effect to reduce traffic and railway noise in residental areas. Surveys were conducted at Mok-Dong Apt., Kwa-Choon Apt., Jungbu Express Highway and Kynug-Bu Express Highway for traffic noise and at Mansuk Dong Apt. for railway noise between March 1988 to April. 1990. Noise were measured in accordance with the Standard Examination method for Environmental Pollution. Noise reduction effects of barriers were analyzed at 1 meter in front and back of the barrier. In analyzing factors such as vehicle speed, traffic volume, vehiclemix, road condition and road type are taken to identify the relation of traffic noise factors and traffic noise. Traffic and railway noise were considered as point sources. Through the analysis of noise measurements, it was found that there were 15 dB difference in the transmission loss of the barrier between field measurements and reveberation room method. The transmission loss of the barrier were higher for the reverberation room method field measurements When the train is leaving, the noise gradually increases at low frequency and decreases around 2000 H^^z. When the train is approaching, there is a high noise level of between 74 dB(A) and 82 dB(A) at a low frequency 100-1700H^^z. The result shows that over 7-8 d8(A) were reduced up to 3rd floor in Apts areas. The reduction became sharply decreased 7or higher floor. In relation to the Environmental Control Limit of 70 dB for the Japanese railway system, "Shin Kan Sen", the noise level above the 4th floor is shown to exceed this limit by 3.7-7.8 dB. [영문] The study evaluated the barrier effect to reduce traffic and railway noise in residental areas. Surveys were conducted at Mok-Dong Apt., Kwa-Choon Apt., Jungbu Express Highway and Kynug-Bu Express Highway for traffic noise and at Mansuk Dong Apt. for railway noise between March 1988 to April. 1990. Noise were measured in accordance with the Standard Examination method for Environmental Pollution. Noise reduction effects of barriers were analyzed at 1 meter in front and back of the barrier. In analyzing factors such as vehicle speed, traffic volume, vehiclemix, road condition and road type are taken to identify the relation of traffic noise factors and traffic noise. Traffic and railway noise were considered as point sources. Through the analysis of noise measurements, it was found that there were 15 dB difference in the transmission loss of the barrier between field measurements and reveberation room method. The transmission loss of the barrier were higher for the reverberation room method field measurements When the train is leaving, the noise gradually increases at low frequency and decreases around 2000 H^^z. When the train is approaching, there is a high noise level of between 74 dB(A) and 82 dB(A) at a low frequency 100-1700H^^z. The result shows that over 7-8 d8(A) were reduced up to 3rd floor in Apts areas. The reduction became sharply decreased 7or higher floor. In relation to the Environmental Control Limit of 70 dB for the Japanese railway system, "Shin Kan Sen", the noise level above the 4th floor is shown to exceed this limit by 3.7-7.8 dB.
환경관리학과/석사